Airborne bacteria and fungi in different indoor environments: levels and dose rates - Paciência, I. (2017)
The study aimed to: (i) quantify bacteria and fungi concentrations in 4 indoor environments; (ii) identify the recovered fungi; (iii) assess the impact of outdoor bacteria and fungi indoors; and (iv) estimate bacterial and fungal inhalation dose rates in children and elderly. Air samples were collected from 20 primary schools, 68 homes, 9 child day-care centres and 22 elderly care centres, with a microbiological air sampler using TSA and MEA culture media.